Joint Venture Contracts - Pimentel, Dinarco (Revista Jurídica Portucalense, 2015)
Joint Venture contracts are contracting models typically designed to reach international markets. In spite of being used at the national level, a joint venture is based on single or multiple contracts between two individuals, two institutions, two organizations or two different entrepreneurial entities joining forces, meeting synergies to reach a common goal. Initially, these types of contracts were justifiable based on the need of different economic agents penetrating the most inaccessible markets. Today, they are shown as the ideal instrument to pursue a different end, wherein the interest is divided between both parties in order to optimize production processes. The process of entering into a joint venture will allow both parties to split the reward as well as the risk and both parties will share in the fiscal responsibility, risk, and reward. Since the enterprises, and more specifically the business agents, are the economy’s engine, whether national or not, these contracts are shown as mechanisms, both legally and economically, that promote such business development. <span style="font-size: 11pt; font-family: "Verdana",sans-serif; color: black; line-height: 107%; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">According to this information, we will try to approach these types of contracts, preparing an analysis, based on a briefing of this concept.